2010
DOI: 10.1016/j.evolhumbehav.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Altruism toward in-group members as a reputation mechanism

Abstract: To test the hypothesis that sensitivity to monitoring drives people to act altruistically toward members of their own community, two experiments investigated whether an eye-like painting promotes altruism toward in-group members, but not toward out-group members. Participants played the role of dictator in a dictator game with another participant (a recipient) who was from the minimal in-group or out-group. Participants knew if their recipient was an in-group member or an out-group member, but were informed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(124 citation statements)
references
References 46 publications
(45 reference statements)
6
113
2
3
Order By: Relevance
“…Haley and Fessler (25) found that contributions in an anonymous Dictator Game were higher when the computer monitor displayed a pair of stylized eyes than when it displayed plain text. The effects of eyes in the Dictator Game have been replicated (28)(29)(30) and seem to be a function of the expectation of future benefits, not fear of punishment (30).…”
Section: Critiques Of Interpretation Of Behavioral Economics Gamesmentioning
confidence: 92%
“…Haley and Fessler (25) found that contributions in an anonymous Dictator Game were higher when the computer monitor displayed a pair of stylized eyes than when it displayed plain text. The effects of eyes in the Dictator Game have been replicated (28)(29)(30) and seem to be a function of the expectation of future benefits, not fear of punishment (30).…”
Section: Critiques Of Interpretation Of Behavioral Economics Gamesmentioning
confidence: 92%
“…While subjects do allocate more goods to in-group members, they still share significant amounts with out-group members. Second, when the experimental design assures that the recipients of allocations do not know the group membership of the allocator while the allocator does know that he/she is playing with an in-group member, ingroup favouritism can disappear [58,59]. Revealing results were also obtained with respect to third-party punishment of allocators [60,61].…”
Section: (D) Studies On the Psychology Of Human Intergroup Relationsmentioning
confidence: 98%
“…Assessing the strong hypothesis requires an approach with predictions that go beyond saying that reputational cues should increase altruism. Second, though many studies have provided evidence for the importance of payoff-irrelevant social cues (Haley and Fessler, 2005;Bateson et al, 2006;Burnham and Hare, 2007;Rigdon et al, 2009;Mifune et al, 2010;Ernest-Jones et al, 2011;Oda et al, 2011;Francey and Bergmüller, 2012), the evidence overall is mixed. Some studies have also failed to find an effect (Fehr and Schneider, 2010;Lamba and Mace, 2010;Carbon and Hesslinger, 2011;Tane and Takezawa, 2011;Ekström, 2012;Raihani and Bshary, 2012).…”
Section: Introductionmentioning
confidence: 99%